Peranan Pimpinan dan Guru dalam Pembinaan Akhlak Siswa Pada Madrasah Tsanawiyah Negeri Kupang - Marwan Gozali; Muhammad Tamrin (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
This study aims to analyze: 1) leadership policies on student moral development, 2) implementation of teacher guidance in implementing student morals, 3) supporting and inhibiting factors in moral development, 4) The success of teachers in developing student morale. This research was conducted at Madrasah Tsanawiyah Negeri Kupang. This research was conducted with a descriptive analytic method with a qualitative approach. The results showed that the leadership policy towards the moral development of students in MTs. Negeri Kupang, namely by making school regulations that support the development of student morals, the implementation of teacher guidance in developing student morals can be seen from the combination of Islamic religious learning with the delivery of subject matter related to morals and extracurricular activities. The supporting factor for the development of student morals is the existence of regulations. madrasah regarding the obligations of students to take part in extracurricular activities that have been determined by the schedule, the existence of a madrasah leadership policy program related to the creation of school conditions that have a nuanced hospitality, there are inhibiting factors. The success of students' moral development can be said to be less than optimal because the indicators of success are the same as changes in student character for the better.